Molecular Disruption of Ion Transport Peptide Receptor Results in Impaired Water Homeostasis and Developmental Defects in Bombyx mori - Sun, Lili; Zhang, Zhongjie; Zhang, Ru; Yu, Ye; Yang, Fangying; Tan, Anjiang (Frontiers in Physiology, 2020)
Insect ion transport peptides (ITPs) are important regulators of many physiological processes and they exert their functions by interacting with their receptors (ITPRs). However, no such ITPRs have been identified in the model insect Drosophila melanogaster, and therefore the physiological roles of ITPRs in insects are poorly understood. In the current study, we comprehensively investigated the physiological functions of ITPR in the lepidopteran model insect, the silkworm (Bombyx mori), using the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein-9 nuclease (Cas9) genome editing technique. Mutations in silkworm ITPR (BmA2) resulted in a prolongnation of the larval stage by 3.5 d as well as failure in wing expansion of moths. The BmA2 mutation accelerated food transition throughout the digestive tract, which is 1.55-fold that of wild type (WT) insects. Excretion was 1.56-fold of WT insects during the larval stage, resulting in the loss of body water content. Loss of BmA2 function induced significant upregulation of nitric oxide synthase (NOS) enzyme activity and nitric oxide (NO) content, as well as downstream Ca2+/NO/cGMP signaling pathways. Key genes in insulin and ecdysone signaling pathways were also affected by BmA2 disruption. Our data show that ITPR play key roles in regulating insect water homeostasis and development.